Real estate - Dasso, Jerome J. (Prentice Hall, 1995)
This book is written and designed for anyone seeking a clear understanding of the many decisions involved in real estate. The intent is to create a mind set that will make it easier for the reader to understand the world of real estate, and how change and real estate values interact. The material is in four major parts covering important components of the decision-making process: value analysis; market dynamics and property development; finance; and law and brokerage.